Sistem Penjaminan Mutu Internal Dalam Meningkatkan Mutu Di Universitas Sunan Drajat Lamongan - Hidayatul Mufidah (Pusat Riset dan Inovasi Nasional, 2025)
To achieve quality education in higher education, an Internal Quality Assurance System (SPMI) is required, as is the case at Sunan Drajat Lamongan University (UNSUDA). Therefore, this study aims to describe the Internal Quality Assurance System in Improving Education Quality at Sunan Drajat Lamongan University (UNSUDA). In this study, we used descriptive qualitative research methodology. We also used primary and secondary data in this study. The data collection techniques we used were observation, interviews, and documentation. Meanwhile, the data analysis technique used data analysis, starting with data collection, data reduction, to drawing conclusions. The results of the study are as follows: first, UNSUDA's Internal Quality Assurance System (SPMI) uses the plan, do, check, act stages. 1) Plan: UNSUDA has stages of determining policies, determining quality manuals, determining standards, and creating quality forms. However, in determining policy, UNSUDA integrates pesantren values. 2) Do: in this stage, UNSUDA uses improvement-based implementation, collects data, and documents data. It also forms a culture of quality, such as orientation towards stakeholders, teamwork, and a character of responsibility and discipline. 3) Check: in this stage, the Internal Quality Audit (AMI) process is carried out. UNSUDA conducts AMI every year. 4) Act: In this stage, UNSUDA carries out two activities: quality control and improvement. Quality improvement at UNSUDA includes developing a doctoral program (S-3). Overall follow-up actions are presented in the form of a follow-up plan. Second, the quality of education is viewed from the aspects of output, service, human resources (HR), service, process, and environment. Therefore, SPMI at UNSUDA determines the achievement of educational quality because it is SPMI that will improve the quality of each university and shape the culture of quality of a university. The quality of education at UNSUDA has improved after the implementation of SPMI. Overall, the quality at PTKIS has improved and will even become the identity of educational quality or the uniqueness of educational quality and be used as branding at every PTKIS, thereby becoming the competitive advantage of PTKIS over private universities (PTS) and other PTKIS.